Penerapan Metode Scramble untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Yus Yusuf Zaini Taziri; Tarsinah (Sekolah Tinggi Agama Islam Persatuan Umat Islam Majalengka, 2026)
This research was motivated by low student learning outcomes due to teacher-centered learning methods using lectures, resulting in suboptimal student participation and engagement. The Scramble method was chosen because it can create active, creative, and enjoyable learning, as well as encourage collaboration and rapid thinking. This study aims to determine the improvement in student learning outcomes in Islamic Religious Education (PAI) subjects through the application of the Scramble learning method in class VIII C of SMPN 5 Majalengka in the 2024/2025 Academic Year. This study used a Classroom Action Research (CAR) design implemented in two cycles. The subjects were 18 students of class VIII C. Data were collected through observation, learning achievement tests, and documentation. Data analysis was conducted using descriptive quantitative and qualitative methods. The results of the study indicate that the application of the Scramble method can improve student learning outcomes in the topic